2008
DOI: 10.1111/j.1440-1681.2008.04983.x
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation by Nicotine of the Cyclosporine A‐induced Impairment of Β‐adrenoceptor‐mediated Renal Vasodilation in Rats

Abstract: Nicotine is implicated in smoking-related renovascular impairment and worsening of existing nephropathies. In the present study, we investigated whether nicotine aggravates the deleterious effect of the immunosuppressant drug cyclosporine A (CsA) on renal vasodilation induced by the beta-adrenoceptor agonist isoprenaline. Bolus isoprenaline (0.03-8.0 micromol) elicited dose-dependent vasodilation of phenylephrine-preconstricted perfused kidneys that was attenuated by infusion at 5 mL/min of nicotine (5 x 10(-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
(126 reference statements)
0
9
0
Order By: Relevance
“…Because nicotine was administered in single daily doses, it could be argued that the rapid elimination of nicotine might have hampered the development of hypertension. Remarkably, the single daily-dose regimen has been repeatedly used for studying the biological effects of nicotine (Hui and Ogle, 1991;Ferrari and Fior-Chadi, 2007;El-Gowilly et al, 2008). Moreover, pharmacokinetic studies showed that, despite the relatively short half-life of nicotine (ϳ1 h), the half-life of cotinine, the principal metabolite and pharmacologically active form of nicotine, ranges from 10 to 24 h (Miller et al, 1977;Buccafusco and Terry, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Because nicotine was administered in single daily doses, it could be argued that the rapid elimination of nicotine might have hampered the development of hypertension. Remarkably, the single daily-dose regimen has been repeatedly used for studying the biological effects of nicotine (Hui and Ogle, 1991;Ferrari and Fior-Chadi, 2007;El-Gowilly et al, 2008). Moreover, pharmacokinetic studies showed that, despite the relatively short half-life of nicotine (ϳ1 h), the half-life of cotinine, the principal metabolite and pharmacologically active form of nicotine, ranges from 10 to 24 h (Miller et al, 1977;Buccafusco and Terry, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine also cause renal vasoconstriction and damage probably via increasing levels of vasoconstrictors, such as catecholamines, vasopressin and endothelin-1 [17]–[19]. Further, nicotine impairs NOS-dependent [20] and β-adrenoceptor vasoreactivity [21], [22] These discrepant vascular effects of nicotine could be attributed to differences in vascular beds or in the dose or duration of nicotine regimens.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that most of the published work on the vascular effects of nicotine has been conducted in the male population [11], [17], [21] or in pooled populations from both genders [16]–[19]. We have recently demonstrated that estrogen enhances the vasodilator effect of acute nicotine in the renal vasculature of female rats mainly through facilitation of NOS signaling [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, only one experimental study has reported the simultaneous effects of CsA and nicotine on renal function [21]. These authors demonstrated that the concurrent administration of CsA and nicotine exacerbated functional vascular impairment and renal dysfunction as compared with the administration of each substance separately.…”
Section: Discussionmentioning
confidence: 99%